Strategi Pengembangan Kualitas Sumber Daya Manusia di Kelurahan Batunadua Jae Padangsidimpuan - Harianja, Nurbaya; Patriansyah, Wawan; Juniasih, Tri Eva; Lona, Rina Tiur (prodima@fe.uika-bogor.ac.id, 2022)
Human resources are very important to know in running the wheels of government so that the vision and mission can be achieved. The purpose of this study was to find out what strategies were carried out by the Lurah and employees at the Batunadua Jae village office, Padangsidimpuan City in developing the quality of human resources in this case employees and what were the supporting factors and inhibiting factors for the development of human resources. Based on the results of research with interviews with 8 employees, including the Lurah, it was found that human resource development activities have not been running optimally. Of the 8 employees, only 4 people or 50% have implemented or participated in human resource quality development activities. The activities that have been followed include training or technical guidance on public administration and services. Another development is leadership training which is only attended by the Lurah and the Secretary of the Lurah. The supporting factor for the development of the quality of human resources is the number of activities available both by the government and the private sector. The inhibiting factor experienced is the lack of interest and funds needed by employees in participating in human resource quality development activities.